Mission's public engagement: The conversation of missiology and public theology. Issue 1 (January 2017) - Kim, Sebastian
The recent development of public theology, the formation of the Global Network for Public Theology, and active scholarly discussions through the platform of the International Journal of Public Theology demonstrate that there is significant interest in the public engagement of theology in contemporary society. Public theology could be identified as critical, reflective, and reasoned engagement of theology in society to bring the kingdom of God, which is for the sake of the poor and marginalized. As David Bosch suggests, mission transforms society and at the same time the concept of mission is being transformed as the church interacts with the wider society. This article aims first to highlight some key features shared by missiology and public theology; second to discuss ways and means to enhance each discipline in its engagement in society, particularly as regards the common good; and third to explore a possibility of "public missiology" or "missiology of public life" in the context of secular and multicultural societies.